Women Against Children: Early Childhood Education and the Domestic Community in Post-Suharto Indonesia. Issue 2 (26th June 2014) - Newberry, Jan
Abstract In response to global attention to the young child, early childhood programs have become a national and provincial focus in Indonesia since 2000. The roll out of public programs for low income communities has made use of a longstanding mode of delivery: the volunteered, community-based labour of women. Although susceptible to analysis as a mode of governmentality, an older scholarship on the domestic community, its role in social reproduction, and its shaping by global accumulation offers significant insights as to why this method for delivering social welfare persists, even as it dovetails with more recent work on care and networks of global care labour. Based on ethnographic work in Yogyakarta, this examination of changes in international development regimes considers the contradictory effects for the empowerment of women as against children. Ultimately, the care labour required for early childhood programming, which has been taken to follow from the naturalised link between women's socially appropriate care work and childrearing, provokes instead questions about the awkward relationship between children and women. That is to say, recent developmental regimes seem to promote the empowerment of children as against women. By foregrounding social reproduction, this awkward relationship becomes a productive way to consider the limits of governmentality and to reconsider the domestic community as critical to understand globalisation, neoliberalisation, and the reorganisation of development and social welfare in the early twenty-first century.